Immersive worlds: an exploration into how performers facilitate the three worlds in immersive performance. Issue 2 (4th May 2018) - Hogarth, Sarah; Bramley, Emma; Howson-Griffiths, Teri
Abstract : This research considers the notion that the immersive performance event consists of three worlds – the fictional, the now and the imaginary ‒ and how an understanding of the qualities of these three worlds, in particular the now and the imaginary, are instrumental to a performer's training in creating immersive theatre. To do this, the research draws upon facilitation techniques from applied drama, mapping some of the fundamental skills required from a performer making immersive theatre that has yet to be articulated by the field. It argues that the use of core facilitation skills such as rapport, listening, reading micro gestures and effective questioning, can be used by the performer to effectively manage the demands of the now and the imaginary worlds. To illustrate this, the article examines a creative training day with recent graduate drama students from Liverpool John Moores University (LJMU) and students from the Community Drama degree at Liverpool Institute of Performing Arts (LIPA), as well as drawing upon the authors' collective experience of creating and performing in immersive theatre. A key insight from the training day was for student/performers to gain an understanding into the audience members' experiences in immersive performance and how this consideration impacts on the performer's practice. The findings are significant for companies, directors and performers interested in utilising immersive theatre to inform the creation of immersive work.